The Wynberg centre : an evaluation of its potential future within the metropolis of Cape Town - Del Mistro, Romano Franco (School of Architecture, Planning and Geomatics, 2020)
This thesis was prompted by three major concerns. Firstly there is need for a structure of centres providing a wider range of facilities closer to home. Secondly, the Wynberg centre is slowly changing to become almost exclusively a shopping centre, and thirdly, the quality of the environment of the centre is also declining. The first aspect of the analysis was the establishment of what those qualities are that make a centre. Having examined the existing Wynberg centre structure and operation;and · the plans, mainly road schemes, presently proposed by the local authority it became apparent that with these influences the centre of Wynberg would definitely not develop into the centre which was needed. A further six alternatives were prepared to determine the possible future for Wynberg. In the first four alternatives, the involvement presently practiced by the local authority was considered to be a fix and the alternatives were mainly achieved by keeping or omitting one or both of the two road schemes to be built through Wynberg viz. the Wynberg ByPass and the Widening of the Main Road. The second set of alternatives was based on the premise that the Local Authority would become actively involved in the development of the centre, able to use economic and legal techniques to induce development in the direction of the goals. An economic and analysis was undertaken to give quantitive values to the alternatives.